The Impact of Preoperative Opioids on Outcomes in Craniotomy Patients. (1st September 2019) - Shah, Varun; Hoang, Nguyen; Rodgers, Brandon; Dornbos, David L; Eaton, Ryan; Pezzutti, Dante; Hoover, Erin; Duenas, Helen; Cua, Santino; Nimjee, Shahid Mehdi
Abstract: INTRODUCTION: There is an unprecedented opioid epidemic in the United States with the rate of drug overdose deaths tripling between 2000 and 2014. The literature suggests that preoperative opioid exposure prior to any surgery independently predicts poorer surgical outcomes. There is a paucity of research on preoperative opioid use and craniotomies. This study proposes to characterize the effects of opioid use on craniotomy outcomes, and triangulate epidemiological sources that predispose patients to adverse outcomes. METHODS: From January 1, 2013 to October 1, 2018, 861 craniotomy patients were identified by CPT codes. Relevant medical and surgical information was extracted from the electronic medical record. Adverse outcomes and readmissions were recorded within 90 d of discharge. Opioid use was recorded by converting dosage into a milligram morphine equivalent (MME) using the Oregon Health Authority online calculator. Regression analysis determined significant factors impacting postoperative outcomes. RESULTS: Patients receiving opioids preoperatively were more likely to be prescribed higher MMEs postoperatively (beta = 0.445, 95% CI 0.320-0.569; P < .001) and at discharge (beta = 0.151, 95% CI 0.069-0.232; P < .001). Preoperative MME significantly impacted postoperative respiratory failure (OR 1.004, 95% CI 1.002-1.006; P < .001) and pneumonia (OR 1.005, 95% CI 1.002-1.007; P < .001). Preoperative MME positively correlated with an increased length of stay (LOS) (beta = 0.024, 95% CI 0.014-0.034, P < .001). Preoperative MME did not correlate with other adverse outcomes. Employment and insurance status lacked correlation with preoperative MME. CONCLUSION: Craniotomy patients with higher preoperative MMEs are more likely to suffer from respiratory failure, pneumonia, and have a longer LOS compared to the no-opioids group. Our findings show that these patients should be more closely monitored for these negative events postoperatively. The lack of significance with other outcomes suggests that other factors impact negative outcomes in the opioid-exposed craniotomy population. Future work should further elucidate the mechanisms behind adverse events in this patient population.